Compartmentalized metabolic engineering for biochemical and biofuel production. Issue 6 (2nd May 2017) - Huttanus, Herbert M.; Feng, Xueyang
Abstract: Sub‐cellular compartments create specialized reaction chambers in eukaryotes. These compartments provide favorable micro‐environments for many metabolic processes. Recently, metabolic engineers have explored the concept of pathway compartmentalization to enhance the performance of metabolic pathways. This strategy offers many unique advantages, including (i) increased local concentrations of enzymes and substrates, (ii) accessing alternate substrate pools, (iii) separation from competing reactions, and (iv) isolation of harmful intermediates or conditions needed for the pathway. In this review, the method of localizing metabolic pathways into specific organelles as well as the benefits of pathway compartmentalization in terms of enhancing the production of value‐added chemicals is discussed. Abstract : Sub‐cellular compartments provide favorable micro‐environments for many metabolic processes. In this mini‐review, the benefits of pathway compartmentalization in terms of enhancing biochemical and biofuel production is summarized. Various methods of enzyme localization are discussed along with some specific applications of compartmentalized metabolic engineering strategies.